THE COMPARISON OF DISCLOSURE OF ISLAMIC VALUES IN ANNUAL REPORTS OF SHARIA BANKS IN INDONESIA AND MALAYSIA - Moh Sigit Awwaludin; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims at comparing the level of disclosure of Islamic values in Islamic banks in Indonesia and Malaysia. The method used in research is a quantitative method using descriptive analysis techniques and test of difference. The data used in this study are secondary data, namely the annual reports of Islamic banks in Indonesia and Malaysia in 2013-2017. The disclosure aspects of Islamic values in the annual report of Islamic banks that became the focus of this study are information regarding the vision and mission, the top management information, service and product information, zakat, donation and charity, employee support, commitment to debtors, commitment to the environment and society, and evaluation of the Sharia Supervisory Board (DPS). The result of this study indicates that there are differences in the level of disclosure of Islamic values in Islamic banks in Indonesia and Malaysia. Based on the results of statistical tests show that the average disclosure of Islamic values in Islamic banks in Indonesia is better than Islamic banks in Malaysia. The difference in the level of disclosure is due to the status of several Islamic banks in Indonesia as publicly owned companies.Keywords: Disclosure of Islamic Values, Annual Report, Islamic Bank.REFFERENCEAAOIFI. (2015). Shariah standards. Bahrain: Dar Almaiman.Antonio, Muhammad Syafi’i. (2001). Bank syariah dari teori ke praktik. Jakarta: Gema Insani Press.Ariyanto, Taufik. (2014). Analisis pengaruh pengungkapan identitas etis islam terhadap kinerja keuangan bank syariah di Asia. Jurnal Akuntansi dan Keuangan, 1(1), 98-110.Ascarya & Yumanita, D. (2005). Bank syariah: gambaran umum. Jakarta: Bank Indonesia.Ascarya. (2006). Comparing Islamic banking development in Malaysia and Indonesia: Lesson for instrument development. Jakarta: Paper  presented on periodicdiscussion directorat of monetary management Bank Indonesia.Belkoui, Ahmed. (1984). Economic, political and civil indicators and reporting disclosure adequacy: empirical investigation. Journal of Accounting and Public Policy, 3(3), 249-250.Evans, Thomas G. (2003). Accounting theory: contemporery accounting issue. USA: South Western.Fauziyah & Siswantoro, D. (2016). Analisis pengungkapan identitas etika islam dan kinerja keuangan perbankan syariah di Indonesia. Lampung: Simposium Nasional Akuntansi XIX.Hannifa, Ross and Muhammad Hudaib. (2007). Exploring the ethical identity of islamic bank via communication in annual report. Journal of Business Ethics, 7(76), 97-116.Hannifa, Ross. 2002. Social reporting disclosure an Islamic prespective. Indonesia Management & Accounting Research, 1(2), 128-146.Harahap, Sofyan Syafri. (2002). The Disclosure of Islamic Values – Annual Report The  Analysis of Bank Muamalat Indonesia’s Annual Report. University of Leeds:Emerald Group Publishing Limited.Hendriksen, E.S., dan M. Breda. (2000). TeoriAkunting (terjemahan). Edisi Kelima. BukuKesatu. Batam: Interaksara.Muhammad. (2008). Sistem dan prosedur operasional bank syariah edisi revisi. Yogyakarta: UII Press.Salma, Ema. (2017). Nilai – nilai Islam pada bank berbasis syariah. Skripsi tidak diterbitkan. Makassar: UIN Alauddin Makassar.Setiawan, A. (2017). Analisisfaktor-faktor yang mempengaruhi pengungkapan informasi sukarela pada bank umum di bursa efek Indonesia. SIKAP, 1(2), 90 – 96.Sugiyono. (2017). Metodologi penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.Surat Keputusan Direksi Bank Indonesia Nomor 32/37/KEP/DIR/1999 Tahun 1999 tentang prinsip operasional bank syariah. Jakarta: Bank Indonesia.Suta & Laskito, H. (2012). Analisis faktor-faktor yang mempengaruhi luas pengungkapan informasi sukarela laporan tahunan (studi empiris pada perusahaan manufaktur yang terdaftar pada bursa efek indonesia tahun 2008-2010).Diponegoro Journal of Accounting, 1(1), 1-15.Undang-Undang Republik Indonesia Nomor 10 Tahun 1998 tentang perubahan atas Undang-Undang Nomor 7 Tahun 1992 tentang perbankan.Undang-Undang Republik Indonesia Nomor 21 Tahun 2008 tentang perbankan syariah.